The inspection visit at risk of extinction - Ignacio Polo Martínez (ADIDE Federación, 2018)
The Superintendent of Education has among its many duties the observance (visiting the centers) of the duties of those involved in the teaching and learning processes. Historically, the Superintendent has visited classrooms to observe the process of learning and to evaluate the teaching practice. However, this type of visit does not produce valid results. Some authors call attention to those types of visits whose inspectors just act as interviewers or to fulfill a duty of presence. This type of visit has nothing to do with the functions and powers of the Superintendents or the improvement of the educational system. Currently, main studies reviewed at the national and international level call for the development of an Inspection dedicated to supervision and control from the organizational and pedagogical point of view, of the function of the educational centers. Despite this evidence, there is a general trend to reduce the number of Inspection visits and replace them with other supervision alternatives based on document review (bureaucratic tasks). The main risk for the inspection would be that connected primarily to said bureaucratic tasks and with significant deficiencies in its formation to intervene in the centers, both could imply a necessary substitution by other more efficient agents. This article defends the need to improve the training of the Inspectors, considering that no other element of the educational system has the authority to advise and ensure compliance, in centers, educational services and programs, laws, and established regulations. This is the main point to guarantee the quality of the inspection visit as an axis in which to assess and verify the improvement of teaching, and therefore, the educational system.